Studi Isoterm, Termodinamik Dan Kinetika Adsorpsi Zat Warna Direct Brown Menggunakan Hidroksiapatit Defisien Kalsium - Delita, Fuji; A, Yelmida; Herman, Syamsu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Dye waste produced by industries contains dangerous and poison materials that could pollute the environment. In this study, hydroxyapatite calcium deficient will be used as medium of adsorption. This process will determine the isotherm models, thermodynamic, and adsorption kinetics models. The dye adsorption process was carried out at various temperatures and initial concentration of dye at a rotating speed of 250 rpm. The maximum adsorption capacity raised at a concentration of 10 ppm and temperature of 30ᵒC with the adsorption capacity of 87.5%. The isotherm model of the direct brown dye adsorption process follows the Langmuir model, since the Langmuir model with R2 approaching to 1 at all variation of temperatures. The adsorption kinetic model of direct brown followed the pseudo second order with 0.9992 of R2 used 40ᵒC of temperature, the initial concentration of direct brown solution was 40 ppm with an adsorption rate constant of 0.052. This study applied physical adsorption which using heat capacity of adsorption (ΔH) of -40,94 kJ / mol which is an exothermic process. Key words : Adsorption, Hydroxyapatite, Konsentration, Dye.